Data from Paper "False-Positive Psychology: Undisclosed Flexibility in Data Collection and Analysis Allows Presenting Anything as Significant". Issue 1 (21st February 2014) - Simmons, Joseph P.; Nelson, Leif D.; Simonsohn, Uri
The data includes measures collected for the two experiments reported in "False-Positive Psychology" [1 ] where listening to a randomly assigned song made people feel younger (Study 1) or actually be younger (Study 2). These data are useful because they illustrate inflations of false positive rates due to flexibility in data collection, analysis, and reporting of results. Data are useful for educational purposes.